SDI OTALEX C. 18 Years of Common Work. 9 Years in the Web - Ceballos, F. (2015)
In 2006, among the cross border project Territorial and Environmental Observatory of Alentejo and Extremadura (OTALEX), Alentejo (Portugal) and Extremadura (Spain) regions decided to use SDI as the geographical information platform to exchange cartography and socioeconomic, environmental and territorial harmonized data between the two regions. Such decision was possible due to previous and successful collaboration between these regions and also with Centro Region of Portugal who join the team in 2011, adding 18 years of common work. During many years we assisted to many problems of data harmonization due to the different data sources and collecting and representing methodologies. In 2007, INSPIRE Directive permitted the simplification of methodologies by introducing a common reference system, data and web services standards that allowed interoperability, interchange and data analysis in a more systematic way. Actually SDI OTALEX C is a modular platform with: (1) Private WEB Portal  where partners can manage their own data, services and metadata, defining print templates and geoprocessing models (2) Public WEB Portal (www.ideotalex.eu) with Information about the different cross border cooperation projects, partners and publications INSPIRE standard services view and discover OTALEX C service OTALEX C Indicator System (SIO)  with environmental, economic, social territorial and sustainability indicators and OTALEXC ID OTALEX C linked data.